Physiological Characterization and Assessment of Genetic Variability, Yield, and Quality Properties of Gamma-ray-induced Salinity Tolerant Soybean (Glycine Max (L.) Merrill) Mutants - ATAK, ÇİMEN; ÇELİK, ÖZGE; GÜMÜŞ, TAMER; MERİÇ, SİNAN; AYAN, ALP; Erdoğmuş, Mehmet (Julius Kuhn-Institut Federal Research Center for Cultivated Plants, 2024)
Soybean is an important industrial oilseed plant. As a relatively fast, flexible, cheap, and viable method, mutation breeding, which induces significant random genetic variations, is a widely used method in crop science. In the present study, we investigated physiological parameters, genetic variability, yield, and quality properties of salinity-tolerant mutant plants derived from Ataem-7 and S04-05 soybean varieties by Cs-137 gamma radiation-induced mutations. The SM4 and SM3 mutants exhibited a greater genetic distance than all other salinity tolerant mutants did. SM3 mutant presented 16.8% lower lipid peroxidation under salinity stress. The most significant photosynthetic pigment increase was detected for chlorophyll b in SM4 and SM3 mutants, with values of 1.88 and 2.07-fold, respectively. The SM3 mutant exhibited the highest yield, at 437.6 kg/ha in the M3 generation, while AM1 presented the highest yield in the M4 generation. The AM1 mutant also had the highest pod count by 122.2 per plant. In the AM1 mutant, the photosynthetic pigment increase was 16.69% for chlorophyll a, 37.9% for chlorophyll b and 22.9% for total chlorophyll. These results provide a basis for future investigations in soybean mutation breeding studies for salinity stress tolerance, and also indicate the effectiveness of mutation breeding methods in agricultural breeding programs. © 2024 Julius Kuhn-Institut Federal Research Center for Cultivated Plants. All rights reserved.
Keywords: Fatty Acids; Glycine Max (L.) Merr; Mutation Breeding; Salinity Tolerance